Determinant grammar of the Russian language as an academic grammar of a new type - Olga I. Valentinova; Mikhail A. Rybakov; Lyudmila V. Ekshembeeva (Russian Language Studies, 2023)
The relevance of the research is caused by the need to find a method that provides a complete and systematic presentation of Russian grammar. The aim of the study is to discuss the prospects for creating a grammar that will clarify the reasons for the features of each level of the language and the principle of mutual functional coordination of all levels. Structural and systemic models for constructing grammatical theory became the object of the study, and a comparative systemic analysis of these models was used as a method. The authors show that there are objective prerequisites for the successful creation of a new model of academic grammar - determinant theory of language developed by the founder of modern systemic linguistics G.P. Melnikov. The most stable property of the language system (internal determinant), acquired as a result of its adaptation to the conditions of communication, makes it possible to explain the interdependence of the composition of vowels and consonants, the structure of the syllable, morpheme and word form, the means of syntactic connection of words in a sentence, the features of the internal form of the language, the non-randomness of the composition of grammatical categories and grammatical ways of expressing them. The internal determinant of the inflectional Russian language, formed in the conditions of poor awareness of the interlocutors about each other, formulated as the need to save the length of the speech stream due to the appearance of a large number of joint-meaning morphemes, makes it possible to explain and link such features of the Russian language as the widespread use of internal inflection and fusion, the preparedness of word forms, methods and functions of affixation, the non-randomness of the grammatical categories of tense, person and case, and ways of expressing them. Research prospects are associated with the uniqueness of the determinant approach, which synthesizes the possibilities of typological and historical approaches and makes it possible to establish the meaning and mutually agreed function of each element of the form. Therefore, it allows to create an academic grammar not of a descriptive, but of an explanatory nature.